Factors Driving Resilience in Healthcare Professionals During Public Health Crises: A COVID-19 Perspective - Abdullah Mohammed Almarshad,; Mustafa Ibrahim Alashur,; Naimah Abdulmohsen Almomen,; Kawthar Hussien Alshehab,; Ibtehal Saleh Alajzan,; Entesar Saleh Alabbad,; Nora Abdulrahman Alduhailan,; Sawsan Abduljaleel Alhassani,; Abdullah Mohammed Alsakran,; Abdullaziz Ali Alnowaiser,; Fatemah Abbas Alqattan,; Mohammed Radhi Alessa, (International Journal of Medical Toxicology and Legal Medicine, 2024)
The ability of healthcare workers to bounce back during public health emergencies, such as the COVID-19 pandemic, is essential to maintaining the health and functionality of healthcare systems. This study aims to identify the major determinants of resilience by emphasizing organizational support, work-life balance, stress management, peer support, and perceived preparation. The approach taken was a quantitative survey where the data were collected from 150 medical professionals using a structured, 20-question Google Forms-administered questionnaire. Exploratory Factor Analysis (EFA) was used as the pre-processing phase to test for underlying factor structures in the proposed model and hence check for construct validity, whereas Structural Equation Modeling (SEM) was used to test hypothesized relationships between the variables as well as the general fit of the model. The study's findings show that work-life balance and organizational support are crucial for the development of resilience. More specifically, it was found that peer support moderated the relationship between stress and resilience, while work-life balance mediated the relationship between stress management and resilience. Moreover, it was found that perceived readiness directly benefited resilience. Fit indices of SRMR = 0.04, RMSEA = 0.05, and CFI = 0.92 supported the valid SEM model. Thus, one could conclude that in healthcare workplaces, strengthening peer support networks and work-life balance along with organizational support systems can provide resilience among healthcare workers to cope with stress at workplaces and eventually reduce the consequences of a mental disorder. The study provides useful information for policymakers and health administration to improve the resilience of health care workers while better preparing them for the next public health emergency.